Unusual Presentation of Priapism Associated with Acute and Chronic Myeloid Leukemia in Two Patients: Emergency Management. (13th August 2020) - Gaye, Oumar; Thiam, Ngor Mack; Cassell, Ayun; Gueye, Serigne Mourtalla; Sow, Yaya; Fall, Boubacar; Ndoye, Alain Khassim
Abstract : Priapism is a rare urological emergency. It is rarely a telltale sign of myeloid leukemia. We report two cases of acute myeloid leukemia in a child and chronic myeloid leukemia in a young adult presenting with priapism. Puncture irrigation of the corpora cavernosa followed by systemic treatment to lower the hyperviscosity of the blood due to leukemia provided optimal outcome. Prompt emergency management is required to lower the complication of erectile dysfunction.